2019
DOI: 10.1016/j.jmps.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Hyperelastic phase-field fracture mechanics modeling of the toughening induced by Bouligand structures in natural materials

Abstract: Bouligand structures are widely observed in natural materials; elasmoid fish scales and the exoskeleton of arthropods, such as lobsters, crabs, mantis shrimp and insects, are prime examples. In fish scales, such as those of the Arapaima gigas, the tough inner core beneath the harder surface of the scale displays a Bouligand structure comprising a layered arrangement of collagen fibrils with an orthogonal or twisted staircase (or plywood) architecture. A much rarer variation of this structure, the double-twiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 58 publications
(85 reference statements)
0
34
0
1
Order By: Relevance
“…The BLU fracture toughness has been previously investigated by crack propagation analysis 12,[16][17][18][19] . However, the effect of tilting and off-axis twisting on the laminate fracture toughness should be assessed by further research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BLU fracture toughness has been previously investigated by crack propagation analysis 12,[16][17][18][19] . However, the effect of tilting and off-axis twisting on the laminate fracture toughness should be assessed by further research.…”
Section: Resultsmentioning
confidence: 99%
“…The intricate conformation of the Bouligand laminate unit (BLU) has captured the interest of scientists and engineers, particularly because of its resemblance to laminated composites and its potential for inspiring even stronger, stiffer and tougher synthetic structures [6][7][8][9][10][11][12][13][14][15] . The potential mechanical properties of BLUs have been analyzed by laminate theory 11,12 and fracture mechanics 12,[16][17][18][19] , and by building and testing macroscale models [19][20][21][22][23] . Reproducing BLUs at the microscale, the scale typically found in nature, is still an open ongoing challenge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations revealed that crack twisting mode significantly enhances fracture toughness in the Bouligand architecture where a crack plane propagates following the twisted fiber orientation (27)(28)(29)(30)(31)(32)(33). This amplifies the crack surface area and reorients fibers orientation in response to external loadings (27)(28)(29)33), e.g., tension, bending, or impact loads. The resultant modulus oscillation in the Bouligand structure is also proposed to promote the crack twisting (30).…”
mentioning
confidence: 99%
“…Bouligand structure is composed of superimposed layers of parallel aligned fibers with special angle deviation, which widely exists in the “weapon” or “armor” of animals such as the claws of crab, [ 145,146 ] fish scales, [ 147,148 ] beetle wings, [ 149,150 ] and Mantis shrimp. [ 151 ] Crack propagation paths of Bouligand structure would be longer than “brick‐and‐mortar” structure due to the larger interfacial area perunit crack length, leading to more energy dissipation and a high damage tolerance.…”
Section: D‐printed Biomaterials With Biological Structure Inspirationmentioning
confidence: 99%